The Changing Economy and the Family - Schultz, Theodore W. (Journal of Labor Economics, 1986)
This study is concerned with the impact of changes in economic conditions on the family. "Three issues are considered in this paper. First, the reasons why the family is not fading away as an economic entity are discussed. The argument of this paper is that, despite the declines in various economic functions of the family and the increases in divorces and in other failures, the survival capacity of the family is both strong and robust." Second, the author contends that the economic approach should be extended to deal with the effects of the life-span revolution, shifts in prices and incomes, and the ability of the family to cope with these changes. Third, the hypothesis is put forward that intergenerational transfers are less important than increases over time in real per capita incomes and changes in income composition, its permanent and temporary components, and the sources of income. The geographical focus is worldwide.